The Efficacy, Safety and Tolerability of Retapamulin as a Treatment Option for Impetigo and Other Uncomplicated Superficial Skin Infections: A Meta-analysis - Rudy Ciulianto (The Indonesian Biomedical Journal, 2015)
BACKGROUND: The treatment of impetigo, secondarily infected dermatitis and infected traumatic lesions continue to develop as new generations of drugs are being formulated. Bacteria causing impetigo show growing resistance rates for commonly used antibiotics. Retapamulin being a new drug has been recently approved as topical antibiotic in children and adult. This study aimed to ascertain the efficacy, safety and tolerability of retapamulin as the treatment option for impetigo and other uncomplicated superficial skin infections.METHODS: A search for studies published from 2006-2014 was done in Pubmed, EBSCO, OVID, Science Direct, and Cochrane using the search strategy. The search was limited to studies conducted in human subjects and published in the English language. Randomized controlled trials evaluating the efficacy, safety and tolerability of retapamulin as treatment for impetigo and other uncomplicated superficial skin infections in children and adult were included and extracted independently and the qualities of the studies were appraised using critical appraisal tools. Data analysis was conducted by using RevMan 5.RESULTS: This study has high heterogeneity and found Retapamulin has no statistically significant difference in the clinical success after seven days and follow up among per-protocol-patients, bacteriogical confirmed patients and intention-to-treat patients with impetigo and other secondary infected traumatic lesions compared to other regimens. However, Retapamulin has beneficial effect in the clinical success, well tolerated and safe for children and adults.CONCLUSION: Retapamulin is comparably effective and safe as a treatment option for impetigo and other uncomplicated superficial skin infections.KEYWORDS: efficacy, safety, tolerability, retapamulin, impetigo, meta-analysis